Distributed and Parallel Systems - Kacsuk, Peter (Springer, 2017)
DAPSYS (International Conference on Distributed and Parallel Systems) is an international biannual conference series dedicated to all aspects of distributed and parallel computing. DAPSYS 2008, the 7th International Conference on Distributed and Parallel Systems was held in September 2008 in Hungary.